What do LinkedIn Brazilian Ads ask of Requirements Engineers? - Sousa, Eurizene; Coelho, Murilo; Braga, Roberta; Paixao, Matheus; Spínola, Rodrigo; Mendonça, Manoel; Leite, Julio Cesar; Freire, Sávio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Context. Requirements engineers play a decisive role in the software development process, as they need to understand the application domain and provide good communication with the different project stakeholders. Although the competencies, skills and activities of requirements engineers have already been reported in the literature, it is necessary to investigate what Brazilian software development companies require from software engineers. Aims. To investigate the required technical knowledge, interpersonal skills, and responsibilities expected in the Brazilian job market for software requirements engineers. Method. We performed thematic analysis to examine 41 job ads collected from the LinkedIn Jobs plataform. Results. We found the main terms used for requirements engineers positions. We also recognized 81 technical knowledge and 37 responsibilities expected for requirements engineers. Lastly, we identified 22 interpersonal skills required by the Brazilian software industry. Conclusion. This work organizes the body of knowledge into a conceptual map to support requirements engineers in identifying what the Brazilian software industry expects from them.